PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IVA SD NEGERI 78 PEKANBARU KECAMATAN TENAYAN RAYA - Nismarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
In the background backs Indonesian learning results obtained by the students is very low because the method of learning that are not relevant. Classroom action research aims to determine the implementation of cooperative learning model Numbered Heads Together (NHT) to improve learning outcomes Indonesian grade IV A SD Negeri 78 Pekanbaru on instructional materials do. The experiment was conducted in two cycles each cycle two meetings and one daily tests. Each cycle stages are: planning, implementation, observation and reflection. Data from the activity of teachers and students in the can from the observation sheet, while, learning outcomes in getting the daily test results. The results showed the activities of teachers and students has increased, in the first cycle of meetings I obtained a score of 33 (68.75%), in the first cycle of meetings II obtained a score of 38 (79.17%), the second cycle of meetings I obtained a score of 40 (83 , 33%), and the second cycle II meeting obtained a score of 44 (91.67%). And in the first cycle of the first meeting of student activity data obtained a score of 27 (56.25%), in the first cycle II meeting increased with the acquisition of a score of 36 (75.00%), and the second cycle first meeting increased to 41 (85.42 %), the second cycle II meeting increased to 45 (93.75%). Learning outcomes of students has increased, this is evidenced by: the preliminary data the number of students who reach KKM amounted to 10 students (28.57%) with an average of learning outcomes at 65.37. Increased in the first cycle by the number of students who completed totaling 26 students (74.28%) with an average of learning outcomes at 76.00. And the second cycle increases with the number of students 32 students (91.42%) with an average of learning outcomes at 86.86. Based on these results it can be concluded that the implementation of cooperative learning model NHT can improve learning outcomes Indonesian grade IV A SD Negeri 78 Pekanbaru.